Interstitial pneumonia with autoimmune features - Uma Karjigi; Balebail G Dharmanand (Indian Journal of Rheumatology)
Interstitial pneumonia (IP) or interstitial lung disease (ILD) affect lung parenchyma, and if not treated will lead to irreparable lung damage. Classification of this group of diseases based on the etiology helps in diagnosing and managing these conditions. IP with autoimmune features (IPAF) is the term used for ILD with subtle signs of autoimmune disease but where there is insufficient evidence for it to be categorised as connective tissue disease. This review aims to look at the evidence available so far with regard to the concept of IPAF. It discusses the advantages and limitations of the current criteria, the epidemiology, clinical, radiological, serological features, management aspects, and prognosis of patients who fit into this particular entity.